THE PROSPECT OF FISHING REARING LABOR IN CAGES BUSINESS IN SEDANAU VILLAGES, BUNGURAN BARAT SUBDISTRICT, NATUNA REGENCY, RIAU ISLAND PROVINCE - Vivi Kurniawati; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on March 2015. The research is aim to know the investment costs, gross income, nett income, feasibility and the business prospect of fishing rearing labor in cages in the future. The method used for this research is survey method with the purposive sampling method for determinations of respondent.According to the result of the research, we can see that the result of the financial analysis and the feasibility from the labor as follows : for 10 squares keramba we found Rp 168864333 of total investment, 260400000 gross income, 147605033 nett income, 2.30 BCR and 90.63 FRR. For 8 squares keramba, we found Rp 158153833 of total investment, Rp 279300000 gross income, RpJOM : Vol. 27 Oktober 2015192088667 nett income, 2.65 BCR and 187,20 FRR. For 5 squares keramba we found Rp 102606340 of total investment, Rp 191600000 gross income, Rp 126615360 nett income, 2.94 BCR and 123.40 FRR. Fishing rearing labor in cages in Sedanau Village has a promising prospect seen from the income they got, yet to make a sustainable work for the cultivator in Sedanau Village, it still faced the problem of limited seed from the waters pollution in around.Key Words: Business Prospect, Financial Analysis, Pen Aqua Culture